Cisco Routers for the Small Business - Neumann, Jason C. (Springer, 2017)
Cisco Routers for the Small Business provides, in plain English, a no–nonsense approach to setting up all the features of the Cisco IOS for a small business using broadband technologies. This book explains how to use a Cisco router to setup cable modems, DSL and PPPoE, and explains how to configure NAT, Access Control Lists, Firewalls, DMZs and an IPSec VPN between two sites using advanced encryption. The chapters are tutorial-based and provide easy-to-follow, step–by–step instructions for all tasks that small businesses need to perform using a router. Easy–to–implement example configurations are included in the appendices.